2014
DOI: 10.1089/dna.2014.2527
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-Beta Polymorphisms and Serum Level in the Development of Osteosarcoma

Abstract: The transforming growth factor-beta (TGF-β) signaling pathway plays critical roles in the development of various diseases. The current study investigated whether TGF-β was involved in the pathogenesis of osteosarcoma from the genetic polymorphism perspective and serum level perspective. We first examined two TGF-β1 polymorphisms, rs1800469C/T and rs1800470T/C, in 202 osteosarcoma patients and 216 healthy controls. Data revealed that the prevalence of rs1800470TT genotype and T allele was significantly elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 21 publications
5
37
0
Order By: Relevance
“…This study assessed the relationship between the SNPs (29 T>C, 509C>T, 869 T>C) and osteosarcoma risk, which concludes that only 29 T>C genotype frequency distribution has obvious difference within the patient group and control group as patients carrying TT genotype have higher morbidity of osteosarcoma than patients carrying CC genotype (OR=2.10, 95 % CI=1.08-4.05). In a research including 202 patients with osteosarcoma and 216 healthy controls, Xu and other researchers have found that rs1800470 TT genotype is relevant to the morbidity of osteosarcoma [16], which is in conformity with our research results. Xu made further comparison with the level of serum TGF-β1 between the patient group and control group and thus he found that the patient group has higher level of serum TGF-β1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study assessed the relationship between the SNPs (29 T>C, 509C>T, 869 T>C) and osteosarcoma risk, which concludes that only 29 T>C genotype frequency distribution has obvious difference within the patient group and control group as patients carrying TT genotype have higher morbidity of osteosarcoma than patients carrying CC genotype (OR=2.10, 95 % CI=1.08-4.05). In a research including 202 patients with osteosarcoma and 216 healthy controls, Xu and other researchers have found that rs1800470 TT genotype is relevant to the morbidity of osteosarcoma [16], which is in conformity with our research results. Xu made further comparison with the level of serum TGF-β1 between the patient group and control group and thus he found that the patient group has higher level of serum TGF-β1.…”
Section: Discussionsupporting
confidence: 93%
“…The promoter SNP 509C>T reportedly contributes to osteoporosis by influencing bone mass [14,15]. Xu found that rs1800470TT genotype carriers have higher morbidity rate of osteosarcoma and rs1800470TT genotype patients with osteosarcoma have higher level of TGF-β1 in their serum than rs1800470CC genotype patients [16]. Therefore, we conducted a case-control study to examine whether TGF-β1 SNPs(29 T>C, 509C>T, 869 T>C) modifies osteosarcoma risk and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Altered TGF-β expression was previously observed in patients with metastatic osteosarcoma compared with in patients without metastasis (29). In addition, TGF-β may increase the metastatic potential of human osteosarcoma cells by triggering the malignant phenotype presentation of hyaluronan and versican (30).…”
Section: Discussionmentioning
confidence: 87%
“…However, at levels exceeding 1–2 fg/cell, TGF-β1 may stimulate SMC, fibroblast and chondrocyte proliferation [39]. TGF-β1 is also found in blood serum, although studies aiming to compare TGF-β1 levels and CAD severity yielded conflicting results [5, 4042]; additionally, TGF-β1 levels depend on genetic factors [4346]. Some researchers have associated the C alleles with higher TGF-β1 levels [4446], whereas other authors have postulated higher levels in T/T homozygotes [44].…”
Section: Discussionmentioning
confidence: 99%